2000
DOI: 10.1046/j.1365-2567.2000.00998.x
|View full text |Cite
|
Sign up to set email alerts
|

Tamoxifen alleviates disease severity and decreases double negative T cells in autoimmune MRL‐lpr/lpr mice

Abstract: SUMMARYPrevious study suggested that MRL-lpr/lpr mice treated with tamoxifen (TAM) had less severe proteinuria, reduced serum titre of anti-dsDNA autoantibodies and an increased survival rate. To investigate further the regulatory mechanisms of TAM on MRL-lpr/lpr female mice, a total dose of 200 mg per mice (5 . 5 mg/kg) was given every 2 weeks subcutaneously, while the control mice were injected with oil only. After being treated with TAM four times, the mice were killed and cellular functions were evaluated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 42 publications
3
36
0
Order By: Relevance
“…1, B and C). These results were consistent with those from a previous publication (38). In contrast, cytopiloyne significantly suppressed mouse CD4 ϩ T cell proliferation induced by IL-2/Con A or anti-CD3 Ab in a dose-dependent manner (Fig.…”
Section: H]thymidine Incorporation Assayssupporting
confidence: 93%
“…1, B and C). These results were consistent with those from a previous publication (38). In contrast, cytopiloyne significantly suppressed mouse CD4 ϩ T cell proliferation induced by IL-2/Con A or anti-CD3 Ab in a dose-dependent manner (Fig.…”
Section: H]thymidine Incorporation Assayssupporting
confidence: 93%
“…In agreement with this idea, raloxifene negatively regulated B lymphopoiesis in BM in two separate studies (24,25), and tamoxifen treatment was shown to reduce the severity of autoimmune disease in mouse models (18,22,26). However, the observation that tamoxifen has beneficial effects on autoimmune disease are contradicted by data suggesting that tamoxifen can augment lymphocyte activation (22,27). Regardless, because ER are expressed by many cells of the immune system, including DC (28 -31), it should not be surprising that SERM possess immunomodulatory properties.…”
Section: Endritic Cells (Dc)mentioning
confidence: 86%
“…Furthermore, in vivo exposure of mice to tamoxifen (22) or raloxifene (23) reduced lymphoid organ weights suggesting that these SERM may dampen immune responses. In agreement with this idea, raloxifene negatively regulated B lymphopoiesis in BM in two separate studies (24,25), and tamoxifen treatment was shown to reduce the severity of autoimmune disease in mouse models (18,22,26). However, the observation that tamoxifen has beneficial effects on autoimmune disease are contradicted by data suggesting that tamoxifen can augment lymphocyte activation (22,27).…”
Section: Endritic Cells (Dc)mentioning
confidence: 99%
“…It also decreases serum levels of soluble TNF receptors 55 and 75 (16). In MRL/lpr mice, treatment with tamoxifen decreases the number of CD4 Ϫ CD8 Ϫ T cells (17), whereas in murine lupus induced by 16/6 Id, tamoxifen normalizes the levels of IL-1, IL-2, IL-4, and IFN-␥ (18,46). Other studies investigating the mechanism of action of tamoxifen have shown that tamoxifen decreases CD5 ϩ B cells and inhibits dendritic cell maturation, thereby decreasing T cell activation (16).…”
Section: Discussionmentioning
confidence: 99%